Variation in N2 Fixation in Subarctic Tundra in Relation to Landscape Position and Nitrogen Pools and Fluxes. Issue 1 (1st February 2016) - Diáková, Kateřina; Biasi, Christina; Čapek, Petr; Martikainen, Pertti J.; Marushchak, Maija E.; Patova, Elena N.; Šantrůčková, Hana
ABSTRACT: Biological N2 fixation in high-latitude ecosystems usually exhibits low rates but can significantly contribute to the local N budget. We studied N2 fixation in three habitats of East European subarctic tundra differing in soil N stocks and fluxes: N-limited vegetated peat plateau (PP), frost formations of bare peat called "peat circles" (PC) with high availability of soil N, and vegetated upland tundra (UT) with low to intermediate N-availability. Nitrogen fixation was measured at field conditions twice during summer 2011 by acetylene reduction assay, and N2 fixation rates were verified by 15 N2 fixation assay. Response to variation in nutrients, carbon, and temperature was studied in complementary laboratory experiments. Further, we aimed to link N2 fixation rates to N deposition and major N transformation rates (gross and net mineralization, plant N uptake) including high N2 O emissions recently found from PC. We hypothesized that N2 O emissions in PC were fueled partly by biologically fixed N. Contrary to that hypothesis, N2 fixation was found solely in PP (0.01–0.76 mg N m −2 d −1 ), where N2 was fixed by moss-associated cyanobacteria and heterotrophic soil bacteria. The low N and high P availability corresponded with the occurrence of N2 fixation in these soils. Nitrogen fixation represented only a small portion of plant N uptake in PP. Conversely, bare PC (as well as vegetated UT) lacked N2 fixation and thus N2 O efflux is most likely fueled by release of mineral N to the soil through internal nutrient cycling.